2019
DOI: 10.1016/j.physa.2019.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Examining effect of architectural adjustment on pedestrian crowd flow at bottleneck

Abstract: Recent advances in bottleneck studies have highlighted that different architectural adjustments at the exit may reduce the probability of clogging at the exit thereby enhancing the outflow of the individuals. However, those studies are mostly limited to the controlled experiments with non-human organisms or predictions from simulation models. Complementary data with human subjects to test the model's prediction is limited in literature. This study aims to examine the effect of different geometrical layouts at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…Garcimartín et al [31] calculated the time headway of the sheep herding and adopted power law distribution to quantify the clogging. Referring to pedestrian flows, less congestion is found in the scenario where the exit was at the corner instead of the middle [27].…”
Section: Introductionmentioning
confidence: 98%
“…Garcimartín et al [31] calculated the time headway of the sheep herding and adopted power law distribution to quantify the clogging. Referring to pedestrian flows, less congestion is found in the scenario where the exit was at the corner instead of the middle [27].…”
Section: Introductionmentioning
confidence: 98%
“…With the development of sensor technology and the improvement of microchip computing power, collecting more redundant data and using more realistic methods to simulate the escape process becomes possible [20,21,22,23,24]. It is of practical significance that the disaster may happen in different complex environments [25]. It's natural to introduce the game theory into the evacuation model, for it can include the interaction between people (and environment) selfconsistently [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, it has been observed that, in most cases, the symmetrical doors configurations provide good/optimal results, while only some of the asymmetrical doors configurations provide comparable/better results. The model is configurable and can be used in various scenarios.Symmetry 2020, 12, 627 2 of 25 demonstrated the beneficial effect of such an obstacle, a series of other studies have followed [28], some of them revealing a smaller positive effect [29,30], others stating the influence based on the dimension and position of the obstacle [31], while others proving the ineffectiveness of such a situation [32,33]. In a recent paper, Zuriguel et al [34] studied the effect of an obstacle placed in front of the exit, and the authors concluded that this situation slightly favors the evacuation of the persons near the wall, prompting a debate on the role of the column in an evacuation process.…”
mentioning
confidence: 99%